The Potential and Contribution of the Monument of Ganggawa Sidenreng Rappang and Government Role in Enhancing Its Economic Potential - Nikmatullah Nur; Aisyah Aisyah; Mutiara Indah; Egi Astuti Delia; Alamsyah Agit (Jurnal Pembangunan Nagari, 2023)
The Monument is known for its historic heritage, each region in Indonesia is considered potential for business opportunities by having a monument or historic building. The tourism departement of Sidenreng Rappang managed lots of tourism object and site, one of them is the monument of Ganggawa. Located in Maritengngae the centre of Sidenreng Rappang, the monument of Ganggawa has become one of the most visited monument. The scenery and the atmosphere are very relaxing despite being in the centre of the region. The monument has become culinary tour area, helping local residents by providing the land to sell food, and snack. The purpose of this paper is to explore the impact of the monument of Ganggawa toward local residents economic state, using qualitative method by using open interview as instrument for data collection, this paper will then use deductive reasoning to view the contribution of the monument toward local resident economic state. The finding of this paper will also reflect the government role in supporting the development of the monument of Ganggawa